Effect of the Rehabilitation Program, ReStOre, on Serum Biomarkers in a Randomized Control Trial of Esophagogastric Cancer Survivors - Kennedy, Susan A.; Annett, Stephanie L.; Dunne, Margaret R.; Boland, Fiona; O’Neill, Linda M.; Guinan, Emer M.; Doyle, Suzanne L.; Foley, Emma K.; Elliott, Jessie A.; Murphy, Conor F.; Bennett, Annemarie E.; Carey, Michelle; et al. (Frontiers in Oncology, 2021)
Background The Rehabilitation Strategies Following Esophagogastric cancer (ReStOre) randomized control trial demonstrated a significant improvement in cardiorespiratory fitness of esophagogastric cancer survivors. This follow-up, exploratory study analyzed the biological effect of exercise intervention on levels of 55 serum proteins, encompassing mediators of angiogenesis, inflammation, and vascular injury, from participants on the ReStOre trial. Methods Patients >6 months disease free from esophagogastric cancer were randomized to usual care or the 12-week ReStOre program (exercise training, dietary counselling, and multidisciplinary education). Serum was collected at baseline (T0), post-intervention (T1), and at 3-month follow up (T2). Serum biomarkers were quantified by enzyme-linked immunosorbent assay (ELISA). Results Thirty-seven patients participated in this study; 17 in the control arm and 20 in the intervention arm. Exercise intervention resulted in significant alterations in the level of expression of serum IP-10 (mean difference (MD): 38.02 (95% CI: 0.69 to 75.35)), IL-27 (MD: 249.48 (95% CI: 22.43 to 476.53)), and the vascular injury biomarkers, ICAM-1 (MD: 1.05 (95% CI: 1.07 to 1.66)), and VCAM-1 (MD: 1.51 (95% CI: 1.04 to 2.14)) at T1. A significant increase in eotaxin-3 (MD: 2.59 (95% CI: 0.23 to 4.96)), IL-15 (MD: 0.27 (95% CI: 0 to 0.54)) and decrease in bFGF (MD: 1.62 (95% CI: -2.99 to 0.26)) expression was observed between control and intervention cohorts at T2 (p<0.05). Conclusions Exercise intervention significantly altered the expression of a number of serum biomarkers in disease-free patients who had prior treatment for esophagogastric cancer. Impact Exercise rehabilitation causes a significant biological effect on serum biomarkers in esophagogastric cancer survivors. Clinical Trial Registration ClinicalTrials.gov (NCT03314311).